A retrospective comparison of cyclophosphamide plus antithymocyte globulin with cyclophosphamide plus busulfan as the conditioning regimen for severe aplastic anemia - Ommati,L.V.M. (2009)
Allogeneic hematopoietic stem cell transplantation (AHSCT) is the treatment of choice for young patients with severe aplastic anemia (SAA). The association of antithymocyte globulin (ATG) and cyclophosphamide (CY) is the most frequently used conditioning regimen for this disease. We performed this retrospective study in order to compare the outcomes of HLA-matched sibling donor AHSCT in 41 patients with SAA receiving cyclophosphamide plus ATG (ATG-CY, N = 17) or cyclophosphamide plus busulfan (BU-CY, N = 24). The substitution of BU for ATG was motivated by the high cost of ATG. There were no differences in the clinical features between the two groups, including age, gender, cytomegalovirus status, ABO match, interval between diagnosis and transplant, and number of total nucleated cells infused. No differences were observed in the time to neutrophil and platelet engraftment, or in the risk of veno-occlusive disease and hemorrhage. However, there was a higher risk of mucositis in the BU-CY group (71 vs 24%, P = 0.004). There were no differences in the incidence of neutrophil and platelet engraftment, acute and chronic graft-versus-host disease, and transplant-related mortality. There was a higher incidence of late rejection in the ATG-CY group (41 vs 4%, P = 0.009). Although the ATG-CY group had a longer follow-up (101 months) than the BU-CY group (67 months, P = 0.04), overall survival was similar between the groups (69 vs 58%, respectively, P = 0.32). We conclude that the association BU-CY is a feasible option to the conventional ATG-CY regimen in this population.